Inspection Score and Grading System for Food Services in Brazil: The Results of a Food Safety Strategy to Reduce the Risk of Foodborne Diseases during the 2014 FIFA World Cup - da Cunha, Diogo T.; Saccol, Ana L. de Freitas; Tondo, Eduardo C.; de Oliveira, Ana B. A.; Ginani, Veronica C.; Araújo, Carolina V.; Lima, Thalita A. S.; de Castro, Angela K. F.; Stedefeldt, Elke (Frontiers in Microbiology, 2016)
In 2014, Brazil hosted one of the most popular sport competitions in the world, the FIFA World Cup. Concerned about the intense migration of tourists, the Brazilian government decided to deploy a food safety strategy based on inspection scores and a grading system applied to food services. The present study aimed to evaluate the results of the food safety strategy deployed during the 2014 FIFA World Cup in Brazil. To assess food safety, an evaluation instrument was applied twice in 1927 food service establishments from 26 cities before the start of the competition. This instrument generated a food safety score for each establishment that ranged from 0.0 (no flaws observed) to 2565.95, with four possible grades: A (0.0–13.2); B (13.3–502.6); C (502.7–1152.2); and pending (more than 1152.3). Each food service received a stamp with the grade of the second evaluation. After the end of the World Cup, a study was conducted with different groups of the public to evaluate the acceptance of the strategy. To this end, 221 consumers, 998 food service owners or managers, 150 health surveillance auditors, and 27 health surveillance coordinators were enrolled. These participants completed a survey with positive and negative responses about the inspection score system through a 5-point Likert scale. A reduction in violation scores from 393.1 to 224.4 (p < 0.001) was observed between the first and second evaluation cycles. Of the food services evaluated, 38.7% received the A stamp, 41.4% the B stamp, and 13.9% the C stamp. All positive responses on “system reliability” presented a mean of 4.0 or more, indicating that the public believed this strategy is reliable for communicating risks and promoting food safety. The strategy showed positive results regarding food safety and public acceptance. The deployed strategy promoted improvements in the food safety of food services. The implementation of a permanent policy may be well accepted by the public and may greatly contribute to a reduction in foodborne diseases (FBDs).